Comparison of Neonatal Outcome of Late Pre-Term Neonates Associated with and Without Intrauterine Growth Retardation - Shahid, Hassnain; Ikram, Farooq; Saleem, Maryam; Zulqarnain, Hafiz; Zaman, Saeed; Atif Naseem Abbasi (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the neonatal outcome of late pre-term neonates with and without intrauterine growth retardation at a nursing intensive care unit of our hospital Study Design: Comparative cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital ,Rawalpindi Pakistan, from Jun 2021 to Jan 2022. Methodology: Patients were divided into two groups for comparison, late pre-term neonates with and without intrauterine growth retardation. Intrauterine growth retardation was assessed via ultrasound examination at >29 and <34 weeks of gestation. Neonatal outcome parameters were compared in neonates with and without intrauterine growth retardation. Results: A total of 110 neonates were included in the final analysis. Of them, 69(62.7%) were male, while 41(37.3%) were females. Patients were divided into two groups for the sake of comparison. Fifty-eight (52.7%) had no intrauterine growth retardation, while 52(47.3%) had intrauterine growth retardation. Statistical analysis revealed that longer duration of admission, hypoglycemia and hyperbilirubinemia were found statistically significantly more in late pre-term neonates who had intrauterine growth retardation as compared to those who did not have intrauterine growth retardation (p-value<0.05). Conclusion: Intrauterine growth retardation was a commonly observed finding among neonates who were born at late preterm. Neonates with intrauterine growth retardation were more at risk of certain complications like long stay at the neonatal intensive care unit, hypoglycemia and hyperbilirubinemia